Role ambiguity, role conflict, team conflict, cohesion and collective efficacy in sport teams: A multilevel analysis. (September 2015) - Leo, F.M.; González-Ponce, I.; Sánchez-Miguel, P.A.; Ivarsson, A.; García-Calvo, T.
Abstract: Objectives: This study examines how perceptions of role ambiguity, role conflict, team conflict, and cohesion can predict collective efficacy in sports teams. Design: We adopted a longitudinal perspective, taking measures at the beginning, the middle, and the end of a sport season. Methods: The participants were professional female and male football players, who participated in the First and Second Divisions in Spain. They completed a multi-section questionnaire assessing role ambiguity, role conflict, cohesion and collective efficacy. Results: Multilevel modelling analysis showed that perceptions of team conflict and cohesion, at the interpersonal and interteam levels, can predict changes in collective efficacy. However, individual perceptions of role ambiguity and role conflict were not relevant in establishing a team's confidence. Conclusions: These results suggest interesting practical applications for coaches and sports psychologists in the professional sphere. Highlights: We examined the predictive capacity of group processes on collective efficacy. We used professional football players in a longitudinal design. Team conflict and cohesion can predict changes in collective efficacy. Role ambiguity and role conflict did not emerge as relevant to team confidence.